Tolerance of Religious Life Among Elementary School Students - Sudarjo Abdul Hamid; Tobroni; Nurul Humaidi (South Sulawesi Education Development (SSED), 2024)
Religious tolerance is defined as an attitude of respect and acceptance of different beliefs without imposing personal views. The elementary school environment is one of the important places to instill these values, given the age of students who are still in the character development stage. This research uses a qualitative method with a case study approach to understand how religious tolerance is developed and implemented in the Leuwalang Elementary School environment. Data were collected through observation, in-depth interviews with teachers, students and parents, and document analysis related to school policies on tolerance and diversity. Through a case study approach, this research can describe the application of the value of tolerance in a situation that is concrete, specific and relevant to the local context of the school. Various challenges are faced in fostering religious tolerance in students, including the differences in religious understanding that they bring from home, the lack of understanding of the concept of tolerance at an early age, and the influence of the social environment outside school. The benefits of religious tolerance for students include the creation of harmony in the school environment, the growth of critical attitudes and empathy, and awareness of the importance of living together in a diverse society. By understanding and practicing tolerance, students are expected to become more open individuals who are ready to face challenges in a multicultural society. The results of this study show that religious tolerance not only creates a conducive learning atmosphere, but also shapes the character of students with noble personalities. The application of tolerance values from an early age is expected to create the next generation that is more tolerant, harmonious, and appreciates diversity in social life.